Guerreros, estado y “progreso” en billetes del stronismo (1954-1989) - Roberto L. Céspedes R. (Centre de Recherches sur les Mondes Américains, 2014)
An analysis of banknotes’ iconography of the stronismo (1954-1989) unfolds, on one side, continuity of images of 1952 and, on the other, a new serie with its own features in 1963. They are seven banknotes for nine years but nine banknotes and almost three times span the first one. Within the last seriesremains war heroes of international wars as well as the statemen and founding-fathers, heirs of the former phase of the self-nominated “nationalist revolution” (1940-1946), and a militarist one, we add. The weigth of State icons is almost unchanged while economic icons turn into images of ongoing “progress”. Finally, in a much lesser degree, national war heroes related to the ruling party also are incorporated. Thus, a national imaginary is built up. It is composed by national war heroes and, authoritarian statemen, State symbols and ongoing “progress” are established and enforced by an obligatory circulation process. Summing up,it is an interwoven imaginary of past and present in order to legitimize the actual regime.